Analysis of musculoskeletal disorder due to working postures via dual camera motion capture system - Ngali, Zamani; Jemain, Noratika Budi; Chang, An Wee; Abdol Rahman, Mohd Nasrull; Kaharuddin, Muhammad Zulhilmi; Khairu Razak, Siti Badriah (Penerbit UTHM, 2018)
Ergonomic are known as the study of work. It helps the worker to fit with the environment of the workplace for example the tools, equipment and the work station. Poor ergonomic practice can affect the performance of the worker and the quality of the product besides causing loss to the company. This study have three main purposes which is to establish the optimal set up of the dynamic RULA analysis in UTHM, to compare the performance of static RULA analysis with the current dynamic RULA analysis and to identify the effect of current working posture to the musculoskeletal disorder of the university staffs. The ergonomic tools that was used in this study are Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) and Rapid upper limb assessment (RULA). Besides that, motion captures system and Kinect camera were used for 3D dynamic RULA analysis. Meanwhile, 2D static analysis recorded the video of the subject motion simultaneously to quantitatively compare the result to 3D dynamic analysis. This research found that the 3D dynamic analysis is more accurate compare with the 2D static analysis. This can be proved by comparing the length of the joint point of 2D static analysis and 3D dynamic analysis with the actual length. 3D dynamic method provided 3 axes while the other method only provided 2 axes. 3D dynamic method in this paper was analyzed numerically by a software while 2D static method was analyzed manually by the user and prone to human error and thus not entirely accurate. The result for comparing the performance of the 2D static analysis and 3D dynamic analysis showed that the respondent 1 and 2 have high risk on getting neck pain based on the RULA score. CMDQ analysis showed that the body part of respondent 1 and 2 that are most probably affected by MSD was leg.